(untitled) (Scientific journal of the Fergana State University, 2025)
This article discusses the cultivation environments and preparation technologies of microscopic aquatic plants, particularly the Ankistrodesmus species. Aquatic plants are of significant ecological and economic importance, widely utilized in various industries such as food, biofuels, and others. The article provides a detailed description of theoretical and practical aspects of plant cultivation in artificial environments, the preparation of nutrient media, and methods for stimulating plant growth under the influence of sunlight. Additionally, it covers the composition of nutrients used in the cultivation of Ankistrodesmus, sterilization processes, and scientific methods for monitoring plant growth. Special attention is given to the photosynthetic activity of microscopic aquatic plants and their use in industry, as well as their contributions to new biotechnologies and ecological sustainability.